2020
DOI: 10.1242/jcs.235622
|View full text |Cite
|
Sign up to set email alerts
|

Snail induces epithelial cell extrusion by regulating RhoA contractile signalling and cell–matrix adhesion

Abstract: Cell extrusion is a morphogenetic process that is implicated in epithelial homeostasis and elicited by stimuli ranging from apoptosis to oncogenic transformation. To explore if the morphogenetic transcription factor, Snail (SNAI1), induces extrusion, we inducibly expressed a stabilized Snail6SA transgene in confluent MCF-7 monolayers. When expressed in small clusters (<3 cells) within otherwise wild-type confluent monolayers, Snail6SA expression induced apical cell extrusion. In contrast, larger cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 46 publications
(78 reference statements)
0
17
0
1
Order By: Relevance
“…Studies in Drosophila embryos and in mammalian cells in culture have revealed the importance of cell extrusion in limiting tissue overcrowding and eliminating dying cells to maintain tissue homeostasis and/or determine cell fate ( Kocgozlu et al, 2016 ; Wee et al, 2020 ). Other experiments have shown that a contractile actomyosin ring around the cell cortex is necessary for their extrusion ( Rosenblatt et al, 2001 ; Eisenhoffer et al, 2012 ; Kocgozlu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Drosophila embryos and in mammalian cells in culture have revealed the importance of cell extrusion in limiting tissue overcrowding and eliminating dying cells to maintain tissue homeostasis and/or determine cell fate ( Kocgozlu et al, 2016 ; Wee et al, 2020 ). Other experiments have shown that a contractile actomyosin ring around the cell cortex is necessary for their extrusion ( Rosenblatt et al, 2001 ; Eisenhoffer et al, 2012 ; Kocgozlu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using zebrafish as a model to analyse CM cytoskeletal organization at single-cell resolution, we searched for candidate transcription factors that regulate CM cytoskeletal and tissue integrity. Amongst the transcription factors involved in cardiac development, we focused on Snai1 ( Nieto, 2002 ; Nieto et al, 2016 ), whose orthologues regulate cytoskeletal remodelling and epithelial tissue integrity in Drosophila embryos ( Martin et al, 2010 ; Weng and Wieschaus, 2016 ) and in mammalian cells in culture ( Wee et al, 2020 ). During vertebrate heart formation, Snai1 has been implicated in myocardial precursor migration towards the midline ( Qiao et al, 2014 ) and in valve formation ( Tao et al, 2011 ), but a role in myocardial wall development, during which an epithelial-to-mesenchymal (EMT)-like process occurs ( Staudt et al, 2014 ; Jiménez-Amilburu et al, 2016 ; Priya et al, 2020 ), has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Using zebrafish as a model to analyze CM cytoskeletal organization at single-cell resolution, we searched for candidate transcription factors that regulate CM cytoskeletal and tissue integrity. Amongst the transcription factors involved in cardiac development, we focused on Snai1, whose orthologues regulate cytoskeletal remodeling and epithelial tissue integrity in Drosophila embryos and in mammalian cell culture 911 . Snai1 is required for the migration of myocardial precursors during heart tube formation 6 and for valve formation 5 , but a role in myocardial wall development has not been addressed.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies in Drosophila embryos and in mammalian cell culture have revealed the importance of cell extrusion in limiting tissue overcrowding and eliminating dying cells to maintain tissue homeostasis and/or determine cell fate 11, 23, 24 . Other experiments have shown that a contractile actomyosin ring around the cortex of the cells is necessary for their extrusion 2426 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation